Pencegahan Stunting pada Masyarakat RW 13 Kelurahan Pebatuan Pekanbaru melalui Edukasi Stunting dan Gizi Seimbang Pada Ibu Hamil dalam Program Kerja Praktek Kerja Nyata Mahasiswa Poltekkes Kemenkes Riau - Rosy, Alice; Elmukhsinur, Elmukhsinur; Uthia, Rahimatul (Poltekkes Kemenkes Riau, 2025)
The Stunting is a chronic nutritional problem that has long-term impacts on children's growth and development, as well as the quality of human resources. One of the main strategies in the effort to prevent stunting is to provide education to vulnerable groups, especially pregnant women. This community service activity aims to increase the knowledge and awareness of pregnant women in RW 13 Pebatuan Village, Pekanbaru City, about stunting prevention through balanced nutrition education and early understanding of stunting. The methods of implementation include counseling, interactive discussions, and the distribution of educational media. This activity was carried out as part of the work program of the Community Service Practice of students from Poltekkes Kemenkes Riau. The results of the activity show an increase in pregnant women's understanding of the importance of nutritional intake during pregnancy and steps to prevent stunting. This activity is expected to become a sustainable promotive-preventive effort in supporting the acceleration of reducing stunting rates in the region.